2023
DOI: 10.1186/s12891-023-06213-3
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient proximal medullary filling of cephalomedullary nails in intertrochanteric femur fractures predicts excessive postoperative sliding: a case–control study

Abstract: Objective Excessive postoperative sliding is a common complication of intramedullary nails in the treatment of intertrochanteric femur fractures. The aim of this study was to identify risk factors for excessive postoperative sliding in the intertrochanteric fractures treated with an intramedullary nail. Methods A retrospective analysis of 369 patients with femoral intertrochanteric fractures treated with short intramedullary nails between February … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Jones et al also found a higher reoperation rate in the treatment of stable trochanteric fractures with intramedullary nails, than with SHS [ 26 ]. On the other hand, excessive dynamization of trochanteric fractures, followed by excessive shortening of the femoral offset, should be prevented [ 27 , 28 ]. Excessive dynamization of an extramedullary fixed pertrochanteric fracture could theoretically be found more with SHS or SIF-7, due to the higher range of sliding screws dynamization, than with SIF-10 which contains a mechanism to prevent an excessive dynamization (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al also found a higher reoperation rate in the treatment of stable trochanteric fractures with intramedullary nails, than with SHS [ 26 ]. On the other hand, excessive dynamization of trochanteric fractures, followed by excessive shortening of the femoral offset, should be prevented [ 27 , 28 ]. Excessive dynamization of an extramedullary fixed pertrochanteric fracture could theoretically be found more with SHS or SIF-7, due to the higher range of sliding screws dynamization, than with SIF-10 which contains a mechanism to prevent an excessive dynamization (Fig.…”
Section: Discussionmentioning
confidence: 99%